As práticas de gestão do conhecimento e suas contribuições para a inovação de produtos/serviços em empresas do setor moveleiro - Steinhorst, Jussieli Gregol (2017)
This study deals with knowledge management in the industry, focused on knowledge management practices. By understanding that it is from the knowledge that the innovations arise, in which they are considered source of strategic resource, decision making and business sustainability. The choice of the research universe, the industries of the furniture sector of the Southwest of Paraná, was based on the fact that there are few studies related to knowledge management practices in the industry scenario in the region, besides the existence of a furniture cluster. From this point, it was defined as a general objective of the research, to verify the use and importance attributed to knowledge management practices as a contribution to innovation of products and services in companies of the furniture industry. As specific objectives, it was defined Identify the use of the practices knowledge management in the companies of the furniture sector; Identify the importance of knowledge management practices for product / service innovation in furniture companies. From the literature, the theoretical part was developed which gave support to the work, the questionnaire was applied containing nine questions related to characteristics and profile of companies and 18 questions related to knowledge management practices and two questions about the use of The importance assigned to each practice for innovation. Obtaining 100% return of the questionnaires, we performed Descriptive Statistics, identifying as most used practices we have, Development of a new product / service, Acquisition of new technology, Development of a new process and Intranet / Extranet; By means of the Tukey test, we observed that at a significance level of 5%, nine practices presented statistically significant differences; if we consider the level of 10%, twelve practices presented statistically significant differences; In addition, the overall average use of the practices was 6.26. In relation to the practices attributed as most important for innovation we have, Acquisition of new technology, Groupware / ERP, Development of a new process, Market analysis; It was statistically verified by means of the Tukey test that at a level of 10% of significance, eight practices present statistically significant differences, considering a level of 5% of significance, a practice is no longer statistically significant, in sum the general average of practices Attributed as most important for innovation was 7.38. Pearson's correlation test shows that there is a very strong and positive positive correlation between the variables use and importance attributed to each practice for innovation. Taking into account the general objective of this work, it was evidenced that the practices of knowledge management are contributors to innovation. The results indicate that the companies surveyed recognize the importance of practices for innovation, but they show difficulties in their use, pointing out the need for improvements in their environments so that their benefits are widely exploited. Even so, it is understood that the companies, when using knowledge management practices, being in greater or lesser use averages, are contributing to the process of innovation.